Remembering facts versus feelings in the wake of political events. Issue 5 (4th July 2021) - Levine, Linda J.; Murphy, Gillian; Lench, Heather C.; Greene, Ciara M.; Loftus, Elizabeth F.; Tinti, Carla; Schmidt, Susanna; Muzzulini, Barbara; Grady, Rebecca Hofstein; Stark, Shauna M.; Stark, Craig E. L.
ABSTRACT: Amid rising political polarisation, inaccurate memory for facts and exaggerated memories of grievances can drive individuals and groups further apart. We assessed whether people with more accurate memories of the facts concerning political events were less susceptible to bias when remembering how events made them feel. Study 1 assessed participants' memories concerning the 2016 U.S. presidential election ( N = 571), and included 33 individuals with Highly Superior Autobiographical Memory (HSAM). Study 2 assessed participants' memories concerning the 2018 referendum on abortion in Ireland ( N = 733). Participants rated how happy, angry, and scared they felt days after these events. Six months later, they recalled their feelings and factual information. In both studies, participants overestimated how angry they had felt but underestimated happiness and fear. Adjusting for importance, no association was found between the accuracy of memory for facts and feelings. Accuracy in remembering facts was predicted by media exposure. Accuracy in remembering feelings was predicted by consistency over time in feelings and appraisals about past events. HSAM participants in Study 1 remembered election-related facts better than others, but not their feelings. Thus, having a good grasp of the facts did not protect against bias in remembering feelings about political events.